Proposta de um computador de baixo custo adaptado a fonte de energia híbrida solar-eólica - Vidal, Manoel Victor Meira Lima (2020)
The growing theme of environmental issues is a reflection of a series of anthropic acts that are putting the future of humanity in check. Aspects related to biota pollution, extinction of specimens and extraction of natural resources, have led society to question the future of the planet. Especially this last aspect, whose extraction of these natural resources is directly linked to the generation of energy. Taking into account that the generation of energy is directly related to the development of a nation or organization, the technologies developed by man have been seeking to generate energy through renewable sources, the so-called "clean technologies". In this way, the present work seeks to contemplate this reality in the elaboration of a proposal for a low cost computer through the inclusion of a solarwind hybrid technology, that is, that this computer is developed from components of recyclable origin with pieces of low cost and can be connected to a hybrid solar-wind system, thus ensuring its electrical functioning with full capacity from a renewable energy source. The results of the construction process of the offgrid system and the computer demonstrated that it is possible to elaborate a proposal to create the entire system at low cost. Although there are no number of effects on elements such as power, voltage, current, it is considered that the constructive development of the computer prototype and the offgrid system constituted a significant and healthy advance in a rapid time frame of research. In addition to the fact that it was also possible to carry out a comparative assessment of the system in different climatological periods using data from the Google Earth Engine platform, this fact being fundamental to the continuity of the research on the path this study sought to follow.